The Role and Responsibilities of Notaries in Making Authentic Deeds Based on Forged Letters from the Parties - Kirana Wiguna, Ni Komang Cahya; Bagiastra, I Nyoman (Westscience Press, 2025)
Notaries play an important role in the Indonesian legal system, especially in the making of authentic deeds that have high evidentiary power. One of the main responsibilities of a notary is to ensure the validity of the documents used as the basis for making authentic deeds. However, in practice, it is not uncommon for fake documents to escape the notary's inspection and be used in making authentic deeds. This study aims to analyze the role and responsibilities of notaries in making authentic deeds based on fake letters, as well as the legal risks faced by notaries if they are involved in using fake letters. This study uses a normative research method with a statutory and conceptual approach, which examines laws and regulations related to the position of notary, forgery of letters, and legal responsibilities arising from the involvement of notaries in making deeds based on fake documents. The results of the study indicate that notaries have an obligation to verify the authenticity of documents and the identities of the parties involved, as well as to provide an explanation of the contents of the deed to the parties. If a notary is involved in making an authentic deed based on a fake letter, he can be subject to criminal sanctions in accordance with Article 263 and Article 264 of the Criminal Code, as well as civil liability in accordance with Article 1365 of the Civil Code. This study also highlights the importance of increasing the vigilance and ability of notaries in detecting fake documents to prevent the practice of document forgery which can harm many parties.